The effect of wear on ultrasonic scaler tip displacement amplitude - Simon C. Lea (Blackwell Synergy, 2007)
Aim: During clinical usage, scaler tips may become worn and reduced in length. It is unknown what effect wear has on the magnitude of scaler tip vibrations when they are utilized under typical clinical loads. The aim of this investigation was to assess the effect of simulated wear on ultrasonic scaler tip displacement amplitude, using a scanning laser vibrometer. Materials and Methods: A Cavitron SPS (Dentsply) ultrasonic generator and three scaler insert designs (FSI-100, FSI-1000 and FSI-SLI-10S) were selected for the investigation. Tip vibration displacement amplitude was assessed unloaded and then contacting against tooth surfaces with loads of 0.5 and 1.0 N. Tips were then ground down by 1mm and then 2mm and scans were repeated. Results: For all tips, load and length were found to be significant variables (po0.0001). The scaler tips showed a fall in displacement amplitude with a reduction in tip length. However, all scaler tips showed variability in the amount oscillation that occurred. This was most pronounced with FSI-SLI-10S. Conclusions: This investigation demonstrated that tip wear could affect the performance of dental ultrasonic scaler inserts by reducing their vibration displacement amplitude. Clinicians should be aware of this variability, which may be significant enough to affect clinical procedures.